Viridans Streptococcal Biofilm Evades Immune Detection and Contributes to Inflammation and Rupture of Atherosclerotic Plaques - Pekka J. Karhunen; Tanja Pessi; Sohvi Hörkkö; Vesa Karhunen; Sirkka Goebeler; Anne‐Mari Louhelainen; Mika Martiskainen; Teppo Haapaniemi; Johanna Lappeteläinen; Tommi Ijäs; Leo‐Pekka Lyytikäinen; Emma Raitoharju; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Bacterial DNA from the oral cavity, respiratory tract, gut, and skin has been detected in atherosclerotic plaques, suggesting a role in chronic inflammation linked to atherosclerosis. Chronic bacterial infections often form biofilms resistant to antibiotics and immune detection, giving rise to a new generation of virulent bacteria in suitable conditions. This study explores the role of the immune system in bacterial‐induced inflammation of atherosclerotic plaques. Methods Coronary plaques from 121 sudden death victims and endarterectomy samples from 96 surgical patients were analyzed using bacterial real‐time quantitative polymerase chain reaction, immunohistochemistry, and genome‐wide expression analysis. TLR (toll‐like receptor) signaling was examined in bacterial‐activated TLR cell lines. Results Of the bacteria detected, oral viridans group streptococcal DNA was the most common, being found in 42.1% of coronary plaques and 42.9% of endarterectomies. Immunopositivity for viridans streptococci correlated with severe atherosclerosis (P<0.0001) in both series and death from coronary heart disease (P=0.021) or myocardial infarction (P=0.042). Viridans streptococci colonized the core of the atheroma as a biofilm unrecognized by macrophages of the innate immune system. In contrast, immunopositive streptococci that appeared to have originated from the biofilm infiltrated the ruptured fibrous cap of the atheroma in endarterectomy samples and coronary plaques and were detected by pattern‐recognizing receptors and coexpressed with the adaptive immune response. Among the viridans streptococcal strains, TLR2 was the most activated bacterial‐signaling pathway. Genome‐wide expression analysis of endarterectomy samples showed upregulation of bacterial recognition pathways. Conclusions Latent chronic bacterial inflammation evades immune detection and may contribute to the pathogenesis of complicated atherosclerotic plaques and fatal myocardial infarction.